The concise handbook of analytical spectroscopytheory applications, and reference materials - Workman, Jerry (Singapore : World Scientific Publishing Co. Pte Ltd., 2016)
'The concept of improving the use of electromagnetic energy to achieve a variety of qualitative and quantitative spectroscopic measurements on solid and liquid materials has been proliferating at a rapid rate. The use of such technologies to measure chemical composition, appearance, for classification, and to achieve detailed understanding of material interactions has prompted a dramatic expansion in the use and development of spectroscopic techniques over a variety of academic and commercial fields. The Concise Handbook of Analytical Spectroscopy is integrated into 5 volumes, each covering the theory, instrumentation, sampling methods, experimental design, and data analysis techniques, as well as essential reference tables, figures, and spectra for each spectroscopic region. The detailed practical aspects of applying spectroscopic tools for many of the most exciting and current applications are covered. Featured applications include: medical, biomedical, optical, physics, common commercial analysis methods, spectroscopic quantitative and qualitative techniques, and advanced methods. This multi-volume handbook is designed specifically as a reference tool for students, commercial development and quality scientists, and researchers or technologists in a variety of measurement endeavours. Number of Illustrations and Tables: 393 b/w illus., 304 colour illus, 413 tables.'--
V.1 Ultraviolet spectroscopy -- v.2. Visible spectroscopy -- v.3. Near infrared spectroscopy -- v.4. Infrared spectroscopy -- v.5. Raman spectroscopy.
Title from PDF file title page (viewed July 23, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Spectrum analysis; Electronic books